A high-reflective reinforced black backplane film, preparation method and application thereof
By using a combination of materials such as Cu-MOFs/TiO2/GO composite materials in the photovoltaic backsheet film, the problems of the backsheet film being not resistant to hydrolysis and light aging in high temperature and high humidity environments are solved, and high thermal stability and High infrared reflectivity, extending service life.
Patent Information
- Application Number
- CN202410637642.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-05-22
AI Technical Summary
The photovoltaic backplane film has problems such as not resistant to hydrolysis, not photoaging, poor heat dissipation, poor UV resistance and low reflectivity in high temperature and high humidity environments.
It adopts a highly reflective reinforced black backsheet film including a weather-resistant outer layer, a support layer and a reflective layer. The weather-resistant outer layer is made of PET, black dye, Cu-MOFs/TiO2/GO composite material, silane coupling agent, antioxidant, and ultraviolet light absorption. Composed of stabilizers, tougheners and dispersants.
Improve the thermal stability and infrared reflection rate of the back plate film, extend the service life, and enhance the reflection capacity of the solar light, and reduce the temperature of the back plate surface.
Smart Images

Figure BDA0004852288290000111 
Figure BDA0004852288290000121
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of new materials, and in particular to a high-reflective reinforced black backplane film, a preparation method and application thereof. Background Art
[0002] In recent years, solar energy has received extensive attention as an emerging green renewable energy source. Solar cells are mainly composed of glass, cells, EVA film, backplane film, aluminum frame, junction box and other components. The backplane film is an important material for photovoltaic cell module encapsulation, which protects and supports the cells and requires excellent weather resistance, such as moisture and heat resistance, insulation, waterproofness and stability. The three-layer structure of the backplane film is usually divided into an outer layer, an intermediate layer and an inner layer, and the functions of these three layers are different. The outer layer of the backplane generally uses a weather-resistant fluorine layer or a modified weather-resistant PET, which is directly exposed to the external environment and needs to have good weather resistance and durability; the intermediate layer mainly provides mechanical properties, electrical insulation and barrier properties. The intermediate layer is generally made of PET polyester material; the inner layer of the backplane mainly ensures reliable bonding with the module encapsulation material. At the same time, because sunlight will shine on this layer through the glass, the inner layer needs to have a higher reflectivity to increase the output power of the module.
[0003] Due to the long-term high temperature and high humidity environment of photovoltaic backplanes, photovoltaic backplane films have problems such as poor resistance to hydrolysis, poor light aging, poor heat dissipation, poor UV resistance and low reflectivity. In order to solve these problems, and in order to obtain a visual and architectural effect, high-reflective reinforced black backplane films have attracted the attention of a wide range of researchers. Summary of the invention
[0004] The purpose of the present application is to provide a photovoltaic backplane film with good color stability and thermal stability.
[0005] Another object of the present application is to provide a photovoltaic backplane film with high infrared reflectivity.
[0006] In order to achieve the above objectives, the technical solution adopted in this application is: to provide a high-reflective reinforced black backplane film, including a weather-resistant outer layer, a support layer and a reflective layer, and the weather-resistant outer layer is made of the following materials: PET, black dye, Cu-MOFs / TiO2 / GO composite material, silane coupling agent, antioxidant, ultraviolet light absorption stabilizer, toughening agent and dispersant.
[0007] As a preferred embodiment, the Cu-MOFs / TiO2 / GO composite material is prepared by the following method: first, Cu-MOFs is prepared by copper salt and ligand, graphene oxide, nano-titanium dioxide, the Cu-MOFs, a complexing agent and a cross-linking agent are added into a reaction container, and after the reaction is completed, the product is washed and dried to obtain the Cu-MOFs / TiO2 / GO composite material.
[0008] As another preference, the reflective layer and the weather-resistant outer layer are made of the same raw materials, and the support layer is made of PET, black dye, antioxidant and dispersant.
[0009] As another preferred embodiment, the ultraviolet light absorbing stabilizer is a combination of one or more of phenyl o-hydroxybenzoate, tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) succinate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.
[0010] As another preference, the black dye is a combination of one or more of carbon black, iron oxide black, copper chrome black, iron chrome black, cobalt black, aniline black, oil-soluble black, and perylene black; the antioxidant is a combination of any one or more of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tris(2,4-di-tert-butylbenzene) phosphite, bis(2,4-tert-butylphenyl) pentaerythritol diphosphite, dilauryl thiodipropionate, and 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-carboxybenzyl)benzene.
[0011] Provided is a method for preparing a high-reflection reinforced black backplane film, comprising the following steps: S1: preparing Cu-MOFs using copper salt and a ligand; reacting GO, nano titanium dioxide, the Cu-MOFs, a complexing agent and a cross-linking agent in a container to obtain a reaction product that is a Cu-MOFs / TiO2 / GO composite material; S2: melting PET, the Cu-MOFs / TiO2 / GO composite material, a black dye, a silane coupling agent, an antioxidant, an ultraviolet light absorbing stabilizer, a toughening agent and a dispersant to obtain a weather-resistant outer layer and a reflective layer; melting PET, a black dye, an antioxidant and a dispersant to obtain a support layer; S3: extruding the weather-resistant outer layer, the support layer and the reflective layer through a twin-screw extruder, and obtaining the high-reflection reinforced black backplane film after cooling, shaping and cutting.
[0012] As another preferred embodiment, in S2, 1 to 5 parts by mass of the GO, 2 to 6 parts by mass of the nano-titanium dioxide, 3 to 10 parts by mass of the Cu-MOFs, 1 to 3 parts by mass of the complexing agent and 1 to 3 parts by mass of the cross-linking agent are reacted in a container to obtain a reaction product which is the Cu-MOFs / TiO2 / GO composite material.
[0013] As another preferred embodiment, in step S2, 3% to 7% of the Cu-MOFs / TiO2 / GO composite material, 2% to 5% of the black dye, 1% to 2% of the silane coupling agent, 1% to 5% of the antioxidant, 1% to 8% of the UV light absorbing stabilizer, 1% to 2% of the toughening agent and 1% to 2% of the dispersant are melted according to mass percentage, and the rest is PET, to obtain the weather-resistant outer layer and the reflective layer.
[0014] More preferably, in step S2, according to mass percentage, 2% to 5% of the black dye, 1% to 5% of the antioxidant and 1% to 2% of the dispersant are melted to obtain the support layer.
[0015] Provided is a photovoltaic cell, which comprises, from top to bottom, a photovoltaic backplane, a packaging material, a battery cell, a packaging material and a packaging glass, wherein the photovoltaic backplane comprises the above-mentioned high-reflection reinforced black backplane film, or the high-reflection reinforced black backplane film prepared by any of the above-mentioned preparation methods, and the weather-resistant outer layer is arranged on a side away from the battery cell.
[0016] Compared with the prior art, the beneficial effects of this application are:
[0017] (1) The Cu-MOFs / TiO2 / GO composite material used in the photovoltaic backplane film material of the present application can improve the thermal stability of the film material, and it has long and short external radiation performance, so that the backplane film is heated evenly and is not prone to local heat aging;
[0018] (2) The photovoltaic backplane film material of the present application uses a Cu-MOFs / TiO2 / GO composite material, which is a compound of three materials: Cu-MOFs, TiO2 and GO. The heterojunction can promote charge separation and increase lifespan, thereby improving the surface photoelectric conversion efficiency, broadening the range of light absorption wavelengths, and greatly enhancing the infrared light reflectivity of the photovoltaic backplane film. DETAILED DESCRIPTION
[0019] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.
[0020] The terms "including" and "having" and any variations thereof in the specification and claims of this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.
[0021] The present application provides a high-reflective reinforced black backplane film, comprising a weather-resistant outer layer, a support layer and a reflective layer. The preparation materials of the weather-resistant outer layer include: PET, black dye, Cu-MOFs / TiO2 / GO composite material, silane coupling agent, antioxidant, ultraviolet light absorption stabilizer, toughening agent and dispersant.
[0022] In some embodiments, the preparation method of the Cu-MOFs / TiO2 / GO composite material is as follows: Cu-MOFs is synthesized by a hydrothermal method from copper salt and isophthalic acid; graphene oxide, nano-titanium dioxide, Cu-MOFs, a chelating agent and a cross-linking agent are added to a reaction container, and after the reaction is completed, the product is washed and dried to obtain a Cu-MOFs / TiO2 / GO composite material.
[0023] Metal-Organic Frameworks (MOFs) are organic-inorganic hybrid materials with unique chemical and physical properties. Their structures, such as multiple exposed active sites, ultra-high porosity and crystallinity, provide large specific surface area and uniform cavities. 2+ As a transition element, Cu-MOFs is easy to synthesize, highly active, low-cost, less toxic to organisms, and rich in variable coordination structures. It has the advantages of high conversion rate, high barrier properties, and strong light absorption. It can be used as a material for photovoltaic power generation and has a wide range of application research in the fields of new energy, photocatalysis, optical imaging, and semiconductor materials. The energy bands of composite materials can match each other, and heterojunctions can promote charge separation and increase lifespan, thereby improving surface reaction efficiency, broadening the range of light absorption, and absorbing light in the visible and ultraviolet range. When light irradiates the Cu-MOFs / TiO2 / GO / PET backplane composite film, electron holes are generated, and electrons will make transitions, the carrier transmission rate increases, the photoelectric conversion efficiency is improved, and the range of light absorption wavelengths is broadened, which greatly enhances the service life of the solar photovoltaic backplane.
[0024] Cu-MOFs is an organic-inorganic hybrid material. Due to its high porosity, ultra-high surface roughness and crystallinity, it provides a large specific surface area and uniform cavities. The framework structure increases the active attachment sites for GO and TiO2. In addition, Cu-MOFs has the advantages of high conversion rate, high barrier properties and strong light absorption.
[0025] TiO2 is a semiconductor with the advantages of stable chemical properties, oxidation resistance, high temperature resistance, and high refractive index. TiO2 has a small particle size, large specific surface area, loose and porous, and a rough surface. It is widely used in the photoanode material of dye-sensitized solar cells. Titanium dioxide can effectively prevent the arbitrary growth of microorganisms through photocatalysis, thereby reducing the number of harmful components in the environment. The antibacterial mechanism is that titanium dioxide is activated by light, and the electron-hole pairs and oxygen molecules and hydroxide ions interact with each other, which excites free radicals and causes a chain reaction, destroying the protein of bacteria and achieving the effect of sterilization.
[0026] Graphene oxide is a two-dimensional material that forms a shielding structure in the PET system, slowing down the penetration of substances such as oxygen and water, overcoming the technical defects of PET materials, such as easy degradation, poor water resistance, hydrolysis after long-term contact with water, and acid and alkali resistance. In addition, graphene oxide itself has corrosion resistance and aging resistance.
[0027] Cu-MOFs / TiO2 / GO composite material has a three-dimensional network structure, which plays a supporting role in the matrix material. There are hydrogen bonds and van der Waals forces between the molecules, which greatly enhances the PET system's ability to withstand external forces and reduces losses. PET is a polar polymer, and nanopolymers also have strong polarity. Cu-MOFs / TiO2 2 / The GO composite material is evenly dispersed in the PET system. The combination of the two has better compatibility and greatly improves the mechanical properties of the backplane film. In addition, the Cu-MOFs / TiO2 / GO composite material has high thermal stability and has long and short external radiation properties, which makes the backplane film more evenly heated and less prone to local thermal aging.
[0028] The Cu-MOFs, GO and TiO2 are composited, and the energy bands match each other. The heterojunction can promote charge separation and increase lifespan, thereby improving the surface light conversion efficiency and broadening the range of light absorption wavelengths. The prepared composite film has high visible light and near-infrared light reflection capabilities, greatly enhancing the light reflectivity of the backplane film.
[0029] In some embodiments, the black dye is a combination of one or more of carbon black, iron oxide black, copper chrome black, iron chrome black, cobalt black, aniline black, oil-soluble black, and perylene black.
[0030] In a more preferred embodiment, the black dye is perylene black dye. Perylene black dye has excellent weather resistance, light resistance, solvent resistance, and heat stability. Compared with other pigments, it has a higher reflectivity in the near-infrared band, can absorb ultraviolet light and photo-oxidized free radicals, improve good chemical resistance and light stability, high tinting strength, and is non-toxic and environmentally friendly. In addition, it synergizes with the Cu-MOFs / TiO2 / GO composite material to form a black high-reflection layer, which has a high reflectivity in the near-infrared band (750-1200nm), and the near-infrared reflection factor is greater than 70, which can effectively reduce the absorptivity of the backplane film in the near-infrared band under solar radiation and reduce the temperature of the film surface.
[0031] Perylene pigments are organic pigments with perylene tetracarboxylic acid imide as the parent structure, with excellent light resistance, heat resistance, and solubility resistance, and a wide chromatographic range. In recent years, black varieties, namely perylene black dyes, have been obtained by changing the color molecular structure. The present invention uses Ranbar Black P0086 perylene black pigment, pigment black 32, with a molecular formula of C40H26N2O6 and a relative molecular mass of 630.68, which is a high-performance black perylene black. Compared with other pigments, it has a higher reflectivity in the near-infrared band, can absorb ultraviolet light and photo-oxidized free radicals, improves good chemical resistance and light stability, has excellent light resistance, weather resistance and high heat resistance stability, high tinting strength, high blackness and non-toxic and environmentally friendly, and is used for the preparation of reflective heat-insulating coatings.
[0032] In some embodiments, the ultraviolet light absorbing stabilizer is a combination of one or more of phenyl o-hydroxybenzoate, tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) succinate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.
[0033] In a more preferred embodiment, the ultraviolet light absorbing stabilizer is a mixture of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate and 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.
[0034] Antioxidants refer to organic compounds that can inhibit or delay the thermal oxidation of polymers and other compounds in the air, help capture and neutralize free radicals, thereby removing free radicals and preventing oxidation reactions. In some embodiments, the antioxidant is a combination of any one or more of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tris(2,4-di-tert-butylbenzene) phosphite, bis(2,4-tert-butylphenyl) pentaerythritol diphosphite, dilauryl thiodipropionate, and 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-carboxybenzyl)benzene.
[0035] In a more preferred embodiment, the antioxidant is 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-carboxybenzyl)benzene.
[0036] Light stabilizers are additives for polymer products that can shield or absorb ultraviolet energy, so that polymers can eliminate or slow down the possibility of photochemical reactions under light irradiation. They can be divided into ultraviolet shielding agents, ultraviolet absorbers, free radical scavengers and annihilators. Ultraviolet light absorbing stabilizers selectively absorb ultraviolet rays, convert harmful light energy into harmless light energy through energy transfer, release it in the form of heat, prevent oxidation reactions, and thus prevent or delay aging.
[0037] In some embodiments, the ultraviolet light absorbing stabilizer is a combination of one or more of o-hydroxybenzoic acid phenyl ester, tris (1,2,2,6,6-pentamethylpiperidinyl) phosphite, polysuccinic acid (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) ester, bis (2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis (1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and 2- (2'-hydroxy-5'-methylphenyl) benzotriazole. By absorbing ultraviolet rays and dissipating high energy in the form of harmless heat, the absorption rate of visible light is very small, and the excellent light conversion rate can significantly improve the weather resistance of the coating and improve the light stability of the backplane material.
[0038] This application uses poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate and 2-(2′-hydroxy-5′-methylphenyl) benzotriazole as ultraviolet light absorption stabilizers and 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-carboxybenzyl)benzene as an antioxidant, which work synergistically to greatly improve the weather resistance and yellowing resistance of the backplane film, thereby ensuring the backplane film has a high reflectivity to sunlight. By absorbing ultraviolet rays and dissipating high energy in the form of harmless heat, the absorption rate of visible light is very small, and the excellent light conversion rate can significantly improve the weather resistance of the coating and improve the light stability of the backplane material.
[0039] In some embodiments, the silane coupling agent is any one of -aminopropyl triethoxysilane, -methacrylphthaloxypropyl trimethoxysilane, -glycidyloxypropyl trimethoxysilane, -thiopropyl trimethoxysilane, or a combination thereof.
[0040] In a more preferred embodiment, the silane coupling agent is -methacrylphthaloxypropyl trimethoxysilane. In the present application, -methacrylphthaloxypropyl trimethoxysilane is used as a silane coupling agent. Through the action of the silane coupling agent, coupling bonds are formed between the materials, thereby enhancing the intermolecular forces. At the same time, the adhesion strength of the backplane film is also increased, greatly improving the service life of the solar cell module.
[0041] In some embodiments, the plasticizer is any one of dibutyl phthalate, styrene-butadiene-styrene thermoplastic elastomer, dioctyl phthalate, acrylonitrile-butadiene-styrene copolymer, chlorinated polyethylene, ethylene-vinyl acetate copolymer, or a combination of more thereof.
[0042] In a more preferred embodiment, the toughening agent is a mixture of acrylonitrile-butadiene-styrene copolymer and dioctyl phthalate. In the acrylonitrile-butadiene-styrene terpolymer, acrylonitrile has high hardness and strength, heat resistance and corrosion resistance; butadiene has impact resistance and toughness; styrene has high surface gloss, easy coloring and easy processing; acrylonitrile-butadiene-styrene copolymer and dioctyl phthalate are used as toughening agents for PET composite materials, which greatly improves the mechanical and mechanical properties of the material and enhances the external force impact strength of the material.
[0043] In some embodiments, the dispersant is a mixed solution of sodium dodecylbenzene sulfonate and potassium salt. The dispersant reacts with free radicals to reduce the tendency of polycondensation between silanol groups, further maintaining the stability of the system.
[0044] The reflective layer of the present application utilizes ethylene-tetrafluoroethylene copolymer and dicyclohexylmethane-4,4'-diisocyanate as curing crosslinking agents, which interact and combine with PET to significantly improve the durability and stability of the black photovoltaic backplane in a humid environment. The present application uses hindered phenol antioxidant 330-1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-carboxybenzyl)benzene as an antioxidant, which synergistically enhances the antioxidant properties with perylene black, and is environmentally friendly. The present application uses two ultraviolet light absorption stabilizers, 2-(2'-hydroxy-5'-methylphenyl) benzotriazole and 2-hydroxy-4-n-octyloxybenzophenone, to significantly improve the coating performance and improve the light stability of the photovoltaic backplane material.
[0045] In some embodiments, the reflective layer of the present application is the same as the weather-resistant outer layer of the present application. A small amount of infrared light reflected by the ground will reach the bottom surface of the photovoltaic backplane. This part of the light cannot be effectively utilized. The infrared light will also cause the temperature of the side of the photovoltaic backplane facing the ground to rise. Therefore, the reflective layer also needs to have the function of reflecting infrared light.
[0046] The high-reflective reinforced black backplane film of the present application is thin in material, strong in barrier properties, high in mechanical strength, resistant to aging, strong in resistance to ultraviolet rays, and has good light coverage and high reflectivity. The high-reflective reinforced black backplane film of the present application has a sunlight coverage rate of more than 95%, which greatly extends the service life of the solar backplane.
[0047] The present application also provides a method for preparing a high-reflective reinforced black backplane film, comprising the following steps:
[0048] S1: preparing Cu-MOFs using copper salt and ligand; reacting GO, nano-titanium dioxide, Cu-MOFs, a complexing agent and a cross-linking agent in a container to obtain a reaction product which is a Cu-MOFs / TiO2 / GO composite material;
[0049] S2: Melting PET, Cu-MOFs / TiO2 / GO composite material, black dye, silane coupling agent, antioxidant, ultraviolet light absorbing stabilizer, toughening agent and dispersant to prepare a weather-resistant outer layer and a reflective layer; Melting PET, black dye, antioxidant and dispersant to prepare a support layer;
[0050] S3: The weather-resistant outer layer, the support layer and the reflective layer are extruded through a twin-screw extruder, and after cooling, shaping and cutting, the high-reflective reinforced black backplane film of the present application is obtained.
[0051] In some embodiments, in step S2, 1 to 5 parts by mass of GO, 2 to 6 parts by mass of nano-titanium dioxide, 3 to 10 parts by mass of Cu-MOFs, 1 to 3 parts by mass of a complexing agent and 1 to 3 parts by mass of a cross-linking agent are reacted in a container to obtain a reaction product, a Cu-MOFs / TiO2 / GO composite material.
[0052] In some embodiments, in step S2, 3% to 7% Cu-MOFs / TiO2 / GO composite material, 2% to 5% black silk dye, 1% to 2% silane coupling agent, 1% to 5% antioxidant, 1% to 8% UV light absorption stabilizer, 1% to 2% toughening agent and 1% to 2% dispersant are added in percentage by mass, and the rest is PET, and the weather-resistant outer layer and the reflective layer are prepared after melting.
[0053] In some embodiments, in step S2, 2% to 5% of black dye, 1% to 5% of antioxidant and 1% to 2% of dispersant are melted according to mass percentage to prepare a support layer.
[0054] Example 1
[0055] S1: The Cu(NO3)2·6H2O aqueous solution and the isophthalic acid ethanol solution were mixed evenly and put into a reactor, which was placed in an oven for hydrothermal treatment at 150°C for 3h, cooled and eluted with ethanol water, and vacuum dried to obtain the product Cu-MOFs; 2 parts by mass of GO, 3 parts by mass of nano-titanium dioxide and 6 parts by mass of Cu-MOFs were put into distilled water and stirred, and 1 part by mass of citric acid as a complexing agent and 1 part by mass of ethylene glycol dimethacrylate as a cross-linking agent were added, mixed evenly and transferred to a reactor for reaction, reacted at 160°C for 20h, cooled to room temperature, filtered the product and repeatedly washed with distilled water, and then vacuum dried at 65°C to obtain a Cu-MOFs / TiO2 / GO composite material;
[0056] S2: 5% Cu-MOFs / TiO2 / GO composite material, 6% perylene black dye, 1.2% silane coupling agent, 2.5% antioxidant, 6% UV light absorbing stabilizer, 1% toughening agent, 2% dispersant, and the rest PET were added into a high-speed mixer, mixed and melted at 90°C for 20 minutes to obtain a weather-resistant outer layer and a reflective layer;
[0057] 5% perylene black dye, 2.5% antioxidant, 2% dispersant, and the rest PET were added into a high-speed mixer, and mixed and melted at 80° C. for 20 minutes to prepare a support layer;
[0058] The silane coupling agent is methyl phthaloxypropyl trimethoxysilane. The antioxidant is 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-carboxybenzyl)benzene. The ultraviolet light absorption stabilizer is a mixture of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate and 2-(2ˊ-hydroxy-5ˊ-methylphenyl)benzotriazole. The toughening agent is a mixture of acrylonitrile-butadiene-styrene copolymer and dioctyl phthalate. The dispersant is a mixed solution of sodium dodecylbenzene sulfonate and potassium salt.
[0059] S3: The weather-resistant outer layer, the support layer and the reflective layer are stacked in order, co-extruded through a twin-screw extruder at a speed of 500 rpm and a temperature of 250°C, and after cooling into a sheet, stretched horizontally and longitudinally and heat-set to obtain a high-reflective reinforced black backplane film of the present application.
[0060] Example 2
[0061] The addition amount of Cu-MOFs / TiO2 / GO composite material in S2 was adjusted to 3%, and the rest of the preparation method was the same as in Example 1.
[0062] Example 3
[0063] The addition amount of Cu-MOFs / TiO2 / GO composite material in S2 was adjusted to 7%, and the rest of the preparation method was the same as in Example 1.
[0064] Example 4
[0065] The addition amount of the ultraviolet light absorbing stabilizer in S2 was adjusted to 8%, and the rest of the preparation method was the same as in Example 1.
[0066] Example 5
[0067] The addition amount of the ultraviolet light absorbing stabilizer in S2 was adjusted to 4%, and the rest of the preparation method was the same as in Example 1.
[0068] Example 6
[0069] The addition amount of perylene black dye in S2 was adjusted to 2%, and the rest of the preparation method was the same as in Example 1.
[0070] Example 7
[0071] The amount of antioxidant added in S2 was adjusted to 4%, and the rest of the preparation method was the same as in Example 1.
[0072] Comparative Example 1
[0073] No ultraviolet light absorbing stabilizer is used in step S2, and the rest of the preparation method is the same as that in Example 6.
[0074] Comparative Example 2
[0075] In step S2, no perylene black dye is used, and the rest of the preparation method is the same as that in Example 6.
[0076] Comparative Example 3
[0077] In step S2, 5% TiO2 / GO composite material is used to replace 5% Cu-MOFs / TiO2 / GO composite material, and the rest of the preparation method is the same as in Example 6.
[0078] Performance Evaluation
[0079] 1. Color stability test
[0080] The backsheet films prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were subjected to chromaticity tests according to the HGT 3862-2006 yellow index test method. The chromaticity value b was measured. According to the heat resistance test standard, the yellowing index value △b1 of the sample after baking at 180°C for 30 minutes was measured. According to the UV resistance test standard, the sample was subjected to 120KWh / m 2 The yellowing index value △b2. The results are shown in Table 1. Judgment of color stability test results: the closer the chromaticity value b is to 0, the darker the color; the closer △b is to 0, the better the color consistency.
[0081] Table 1 Color stability test results of photovoltaic backsheets of various embodiments and comparative examples
[0082]
[0083] 2. Photovoltaic backsheet performance test
[0084] The black photovoltaic backsheet films prepared in Example 6 and Comparative Examples 1 to 3 were tested for heat deformation temperature by using a thermal Vicat thermal deformation instrument according to ASTM D648-2000 standard; the reflectivity was measured by ultraviolet spectrophotometry with reference to GB / T 29848 standard; in addition, the photovoltaic backsheets prepared in Example 6 and Comparative Examples 1 to 3 were applied to photovoltaic modules, and the power was measured after aging with reference to standard IEC61215. The results are shown in Table 2.
[0085] Table 2 Photovoltaic backsheet performance test results of Example 6 and Comparative Examples 1 to 3
[0086]
[0087] From the test results in Table 1, it can be seen that the color stability performance of the high-reflective reinforced black backplane film prepared by the present invention is good. After baking at 180°C for 30 minutes, the yellowing index △b1 and 120KWh / m 2 The yellowing index △b2 value is relatively low, and it is not easy to change color, which means that the color consistency is good, and the photovoltaic backboard is not easy to yellow after long-term use. The high-reflective reinforced black backboard film prepared by the present invention has strong color stability in photovoltaic module applications.
[0088] From the test results analysis in Table 2, it can be seen that the use of Cu-MOFs / TiO2 / GO composite materials in the weather-resistant outer layer and the reflective layer in the present application can effectively improve the thermal stability and reflectivity of the photovoltaic backplane film, can reflect more infrared light, increase the effective power of the photovoltaic backplane, and extend the service life of the photovoltaic backplane.
[0089] In addition, adding ultraviolet light absorbing stabilizers, perylene black dyes and Cu-MOFs / TiO2 / GO composite materials to the weather-resistant outer layer and reflective layer can further improve the stability and reflectivity of the photovoltaic backplane material and extend the service life of the photovoltaic backplane.
[0090] The high-reflective reinforced black photovoltaic backplane film of the present application has good color stability and thermal stability, and good infrared reflectivity. The weather-resistant outer layer reflects infrared light, reducing the surface temperature of the photovoltaic backplane, and the reflective layer reflects infrared light to the battery cell, thereby improving the photoelectric conversion efficiency of the photovoltaic backplane assembly.
[0091] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.
Claims
1. A high-reflective reinforced black backplane film, characterized in that: The invention comprises a weather-resistant outer layer, a supporting layer and a reflecting layer. The weather-resistant outer layer is made of the following materials: PET, a black dye, a Cu-MOFs / TiO2 / GO composite material, a silane coupling agent, an antioxidant, an ultraviolet light absorption stabilizer, a toughening agent and a dispersant. The Cu-MOFs / TiO2 / GO composite material is made in the following manner: firstly, Cu-MOFs is made by copper salt and a ligand, graphene oxide, nano titanium dioxide, the Cu-MOFs, a complexing agent and a cross-linking agent are added into a reaction container, and after the reaction is finished, the product is washed and dried to obtain the Cu-MOFs / TiO2 / GO composite material. The reflecting layer is made of the same raw materials as the weather-resistant outer layer, and the supporting layer is made of PET, a black dye, an antioxidant and a dispersant.
2. The high reflective reinforced black backplane film according to claim 1, characterized in that: The ultraviolet light absorption stabilizer is a combination of one or more of phenyl o-hydroxybenzoate, tris (1,2,2,6,6-pentamethylpiperidinyl) phosphite, polysuccinic acid (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) ester, bis (2,2,6,6-tetramethyl-4-piperidinyl) sebacate, bis (1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and 2-(2'-hydroxy-5'-methylphenyl) benzotriazole.
3. The high reflective reinforced black backplane film according to claim 1, characterized in that: The black dye is a combination of one or more of carbon black, iron oxide black, copper chrome black, iron chrome black, cobalt black, aniline black, oil-soluble black, and perylene black; the antioxidant is a combination of any one or more of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tris(2,4-di-tert-butylbenzene) phosphite, bis(2,4-tert-butylphenyl) pentaerythritol diphosphite, dilauryl thiodipropionate, and 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-carboxybenzyl)benzene.
4. A method for preparing a high-reflective reinforced black backplane film, characterized in that: The following steps are involved: S1: preparing Cu-MOFs using copper salt and ligand; reacting GO, nano-titanium dioxide, the Cu-MOFs, a complexing agent and a cross-linking agent in a container to obtain a reaction product which is a Cu-MOFs / TiO2 / GO composite material; S2: Melting PET, the Cu-MOFs / TiO2 / GO composite material, black dye, silane coupling agent, antioxidant, ultraviolet light absorbing stabilizer, toughening agent and dispersant to obtain a weather-resistant outer layer and a reflective layer; Melting PET, black dye, antioxidant and dispersant to obtain a support layer; S3: Extruding the weather-resistant outer layer, the support layer and the reflective layer through a twin-screw extruder, and obtaining the high-reflective reinforced black backplane film after cooling, shaping and cutting.
5. The preparation method according to claim 4, characterized in that: Said S1, reacting 1-5 parts by mass of said GO, 2-6 parts by mass of said nano-titanium dioxide, 3-10 parts by mass of said Cu-MOFs, 1-3 parts by mass of said complexing agent and 1-3 parts by mass of said cross-linking agent in a container to obtain a reaction product which is said Cu-MOFs / TiO2 / GO composite material.
6. The preparation method according to claim 4, characterized in that: In the step S2, 3% to 7% of the Cu-MOFs / TiO2 / GO composite material, 2% to 5% of the black dye, 1% to 2% of the silane coupling agent, 1% to 5% of the antioxidant, 1% to 8% of the ultraviolet light absorbing stabilizer, 1% to 2% of the toughening agent and 1% to 2% of the dispersant are melted according to mass percentage, and the rest is PET, to obtain the weather-resistant outer layer and the reflective layer.
7. The preparation method according to claim 4, characterized in that: In step S2, 2% to 5% of the black dye, 1% to 5% of the antioxidant and 1% to 2% of the dispersant are melted according to mass percentage to obtain the support layer.
8. A photovoltaic cell, comprising, from top to bottom, a photovoltaic backplane, a packaging material, a cell sheet, a packaging material and a packaging glass, characterized in that: The photovoltaic backplane comprises the high-reflection reinforced black backplane film described in any one of claims 1 to 3, or the high-reflection reinforced black backplane film prepared by the preparation method described in any one of claims 4 to 7, and the weather-resistant outer layer is arranged on a side away from the battery cell.
Citation Information
Patent Citations
Humidity-resistant and heat-resistant solar cell backsheet and manufacturing method therefor
US20160329445A1